PENERAPAN MEDIA PEMBELAJARAN VIDEO â€œKASIH IBU KARYA RANGGA KUSMALENDRAâ€ DALAM PEMBELAJARAM MENULIS TEKS DESKRIPSIPADA PESERTA DIDIK KELAS VII SMP NEGERI 32 SEMARANG TAHUN PELAJARAN 2019/2020 - Aan Teguh Febrianto; Harjito Harjito; Mukhlis Mukhlis (Universitas Ngudi Waluyo, 2020)
This research is motivated by language skills that are still low or below average in class VII students of SMP Negeri 32 Semarang, especially in writing descriptive text skills. The form of this research is research with qualitative techniques with descriptive methods. The sample taken in this study is class VII H at SMP Negeri 32 Semarang. Data collection techniques in this study are test and non-test techniques. The test technique used in this study is in the form of a matter of writing description texts by paying attention to the structure of language by using video media to be observed by students. While the non-test technique was obtained by interview and observation by direct observation during the learning process in accordance with the Learning Implementation Plan, namely the initial activities, core activities, and closing activities. Based on test and non-test techniques in the application of video media by Rangga Kusmalendra, it is very appropriate to be used in learning to write descriptive texts in class VII students of SMP Negeri 32 Semarang, 2019/2020 Academic Year, making students interested and enthusiastic in learning. This can be seen from the results of writing description texts as evidenced by the average value of students who reach 81, thus achieving the minimum completeness criteria specified, plus the reaction of students when learning takes place. Suggestions in this study are teachers need to choose and provide media or creative learning models, and can create a fun learning atmosphere. students must pay more attention to learning,Â improve the learning process.Â